Escherichia Coli em vísceras de frangos de corte - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
In the case of poultry, E. coli bacteria can cause several pathological processes, resulting in economic losses and significant health damages, besides determining antimicrobial resistance, a relevant factor for public health. In order to investigate the presence of the bacteria in normal broiler chicken viscera, a study was carried out at a slaughterhouse under a State Inspection System in Goiás. A total of 150 samples were collected, 50 of which were livers, 50 spleens and 50 hearts. bacteriological and histopathological, to verify the microscopic changes determined by the bacterium. In addition, bacterial resistance against the major antimicrobials of importance in poultry and human health was verified: amoxicillin (20 mg), cephalexin (30 mg), ciprofloxaxin (5 mg), enrofloxacin (5 mg), gentamicin mg), sulfamethoxazole-trimetropyr (25 mg), sulfonamide (250 mg) and tetracycline (30 mg). With bacterial growth, 39% (59/150) of the samples were observed, with 23% (35/150) exclusive growth of E. coli, 48, 58% were in the liver, 28.57% in the spleen and 22.85% in the heart. In the antimicrobial susceptibility test, E. coli presented the following resistance rates: sulfonamides (71.43%), tetracycline (60.00%), amoxicillin, cephalexin and gentamicin presented the same resistance percentages (57.14%), enrofloxacin (54.29%), sulfamethoxazole- trimethoprim (28.57%) and ciprofloxaxin (22.86%). In the histopathological examinations the most observed lesion was the presence of inflammatory lymphocytic infiltrates, the liver being the organ with the highest occurrence of these lesions (50/50), followed by hepatic degeneration (12/50). In the spleen the most frequent lesion was rarefaction (4/50) and the lymphocytic inflammatory infiltrate also prevailed in the heart (8/50). Under the conditions of this study, it was concluded that there was high percentage of E. coli isolation in healthy animals, which may have been triggered by pre-slaughter factors related to transport, fasting or prolonged waiting periods, as well as post factors -about as cross-contamination and presence of biofilm in industrial equipment. It was also concluded that there was no relationship between the presence of the bacterium and the tissue changes of the analyzed organs and that resistance to antimicrobial bases occurs frequently, a factor that indicates that drugs should be used rationally only in cases of proven need with the intention of avoiding the triggering of allergies, resistance and toxicity to man.
Keywords: Antimicrobianos; Aves; Bactérias; Microscopia; Sensibilidade; Antimicrobials; Bacterium; Birds; Microscopy; Sensitivity; CIENCIAS AGRARIAS